Variations in the Site of Formation of Basilar Artery - Sultana, Anjuman Ara; Ara, Shamim; Rahman, Mushfika; Afroz, Halima; Fatema, Kanij; Nahar, Nurun; Alam, Md Rafiqul (Bangladesh Journal of Anatomy, 2013)
Context: Basilar artery, supplies the anatomical structures within the posterior cranial fossa of brain. The Circle of Willis is the principal arterial anastomotic trunk of brain formed by the anastomosis between the branches of internal carotid arteries and terminal branch of basilar artery. It is responsible for collateral circulation of brain, specially of old people , who have reduced blood supply to brain due to senile arteriosclerosis . Cerebrovascular diseases due to basilar artery is more common in men than women. Anatomy of basilar artery and its branches are very complex and variable. So, detailed morphogical knowledge is essential for proper diagnosis and treatment of neurological disorder. Objective: To identify variations in the site of formation of basilar artery in relation to age. Study Design: A cross-sectional type of study. Place & period of Study: The study was carried out in the Department of Anatomy, Dhaka Medical College, Dhaka, from January 2010 to December 2010. Materials: 70 postmortem basilar arteries were collected from unclaimed dead bodies that were under examination in the morgue of the Department of Forensic Medicine, Dhaka Medical College Dhaka. The study was approved by the Ethical Review Committee (ERC) of Dhaka Medical College. Methods: The samples were divided into three different age groups i.e. Group A (15 -30 years) Group B (31-45 years) and Group C (46-60 years). Formalin fixed brain was washed with plain tap water to remove excess formalin and was kept on metallic tray. Site of formation of basilar artery was examined carefully by hand magnifying glass and noted. Results: In the present study, 72.2% of basilar artery was formed at pontomedullary junction and 35.7% was formed below pontomedullary junction. Conclusion: In the present study, the commonest site of formation of basilar artery was found at ponto medullary junction and 2nd commonest site was below pontomedullary junction but no formation above pontomedullary junction was found. Further studies to find out the cause and functional / clinical correlations of this variation are recommended. DOI: http://dx.doi.org/10.3329/bja.v10i2.17288 Bangladesh Journal of Anatomy, July 2012, Vol. 10 No. 2 pp 73-75